Evaluation Of 12 Years Of Compulsory Education Policy In Pendopo Barat District, Empat Lawang Regency, South Sumatra Province: Evaluasi Kebijakan Wajib Belajar 12 Tahun Di Kecamatan Pendopo Barat Kabupaten Empat Lawang Provinsi Sumatra Selatan - Hardiansyah, Hardiansyah; Aprianty, Henny; Noviyanto, Hernowo (Gayaku Publisher, 2024)
Based on Decree No. 47 of 2008 of the Government of the Republic of Indonesia concerning Compulsory Education, Article 1(1) states that